EFEK TOKSIK INSEKTISIDA NABATI BERBAHAN AKTIF EUGENOL DAN AZADIRACHTIN PADA KELANGSUNGAN HIDUP DAN PERTUMBUHAN IKAN MAS (Cyprinus carpio) - Masyitoh, Syifa; Yustiati, Ayi; Herman, Roffi Grandiosa; Herawati, Titin; Bari, Ichsan Nurul; Suryadi, Ibnu Bangkit Bioshina (Program Studi Budidaya Perairan, Fakultas Pertanian, Universitas Sriwijaya, 2023)
This research aims to examine the effect of exposure to plant-based insecticides containing active ingredients eugenol and azadirachtin on the survival and growth of common carp (Cyprinus carpio). The study was conducted from September to October 2022 at the Ciparanje Inland Fisheries Hatchery, Faculty of Fisheries and Marine Sciences, Universitas Padjadjaran. The research method used was an experimental method, and the experimental design employed was a completely randomized design (CRD). The study included six treatments with three replications. The test fish used were Majalaya strain common carp fingerling, measuring 7-8 cm, obtained from the Cibiru Fish Seed Center in Bandung City. The treatments examined in this study were Treatment A (0 ppm), B (12.8 ppm), C (25.6 ppm), D (38.4 ppm), E (51.2 ppm), and F (64 ppm). The insecticides were administered once at the beginning of the research in the water, which served as the maintenance medium, according to the treatment concentrations. The parameters observed were survival rate, growth, and water quality. Observations were conducted for 28 days after the application of the plant-based insecticides. The highest percentage of survival was found in Treatment A (control) at 100%, while the lowest percentage of survival was observed in Treatment F (64 ppm) at 81.7%. The highest absolute length growth was recorded in Treatment A (control) at 2.73 cm, and the lowest absolute length growth was observed in Treatment F (64 ppm) at 1.97 cm. The highest weight growth was observed in Treatment A (control) at 4.2 g, and the lowest absolute weight growth was found in Treatment F (64 ppm) at 2.6 g. The research indicates that the growth and survival of common carp fingerling (Cyprinus carpio) decrease due to the influence of exposure to plant-based insecticides containing active ingredients eugenol and azadirachtin.